Biphenotypic B‐cell lymphoma in 2 cats. (13th April 2015) - Granum, Liana; Gorman, Elena; Ruaux, Craig; Vernau, William
Abstract The clinical and pathologic features of biphenotypic B‐cell lymphoma in 2 cats are reported. Clinical presentation varied from multiple cutaneous masses identified on the thigh in one cat to signs of lethargy from acute hemorrhage due to neoplastic infiltration of one kidney in the other. Cytology and histopathology confirmed round cell neoplasia in both cats and immunochemical staining demonstrated expression of both B‐ and T‐lymphocyte markers by the neoplastic cells in both animals. In PCR analysis of antigen receptor gene rearrangement, clonal rearrangement of B‐cell receptor genes and polyclonal T‐cell receptor gene rearrangement were demonstrated in both lymphomas. These findings were consistent with a diagnosis of B‐cell lymphoma with aberrant CD3 expression in both cases. Clinical progression of disease post diagnosis was rapid in both cats, suggesting a poor prognosis for this lymphoma type. Although bigenotypic receptor rearrangement of lymphoma cells appears relatively common, this is the first known report of actual biphenotypic lymphoma in cats.